Homo‐Helical Rod Packing as a Path Toward the Highest Density of Guest‐Binding Metal Sites in Metal–Organic Frameworks. (25th April 2018) - Zhao, Xiang; Shimazu, Matthew S.; Chen, Xitong; Bu, Xianhui; Feng, Pingyun
Abstract: In porous materials, metal sites with coordinate solvents offer opportunities for many applications, especially those promoted by host–guest chemistry, but such sites are especially hard to create for Li‐based materials, because unlike transition metals, lithium does not usually possess a high‐enough coordination number for both framework construction and guest binding. This challenge is addressed by mimicking the functional group ratio and metal‐to‐ligand charge ratio in MOF‐74. A family of rod‐packing lithium–organic frameworks (CPM‐47, CPM‐48, and CPM‐49) were obtained. These materials exhibit an extremely high density of guest‐binding lithium sites. Also unusual is the homo‐helical rod‐packing in the CPM series, as compared to the hetero‐helical rod packing by helices of opposite handedness in MOF‐74. This work demonstrates new chemical and structural possibilities in developing a record‐setting high density of guest‐binding metal sites in inorganic–organic porous materials. Abstract : Zaubertricks von Lithiumionen : Drei Koordinationsstellen genügen den Lithiumionen, um mit Carboxylat‐Phenoxid‐Liganden helikale Ketten aufzubauen. Diese Ketten bilden homochirale Packungen in 3D‐Gerüsten mit einer Dichte an Gastspezies bindenden Metallzentren, die deutlich über derjenigen von MOF‐74 – dem MOF, das diese Struktur imitiert – liegt.